2017
DOI: 10.3390/ijms18050929
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ghrelin System in the Pancreatic Acinar Cells: The Role of the Polypeptide, Caerulein and Sensory Nerves

Abstract: Ghrelin (GHRL) is an endogenous ligand for the growth hormone secretagogue receptor (GHS-R). Experimental studies showed that GHRL protects the stomach and pancreas against acute damage, but the effect of GHRL on pancreatic acinar cells was still undetermined. Aim: To investigate the effect of GHRL and caerulein on the functional ghrelin system in pancreatic acinar cells taking into account the role of sensory nerves (SN). Methods: Experiments were carried out on isolated pancreatic acinar cells and AR42J cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 110 publications
(180 reference statements)
0
11
0
Order By: Relevance
“…Rats were treated with ghrelin given i.p. at single dose of 50 µg/kg or with saline and 48 h later as described previously [ 111 ], animals were again anesthetized with pentobarbital. The abdominal cavity was opened and the pancreas was carefully dissected out from its attachment to the stomach, duodenum and spleen.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were treated with ghrelin given i.p. at single dose of 50 µg/kg or with saline and 48 h later as described previously [ 111 ], animals were again anesthetized with pentobarbital. The abdominal cavity was opened and the pancreas was carefully dissected out from its attachment to the stomach, duodenum and spleen.…”
Section: Methodsmentioning
confidence: 99%
“…It accelerated the healing of oral [ 55 , 56 ], gastric [ 57 ], and duodenal [ 55 , 57 ] ulcers, and colonic inflammation [ 58 , 59 , 60 , 61 , 62 ]. Ghrelin also exhibited a therapeutic effect in animal models of acute pancreatitis [ 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the administration of ghrelin, in animals before the isolation of acinar cells, led to an increase in the expression of ghrelin and the ghrelin receptor in these isolated cells and reversed the cerulein-induce inhibition of their expression. The same effect was observed in AR42J cells after incubation with cerulein and a ghrelin or combination thereof [240]. In addition, studies performed on rats indicate that capsaicin-sensitive sensory nerves are necessary for the protective effect of ghrelin in cerulein-induced acute pancreatitis [241].…”
Section: Protective Therapeutic and Anti-inflammatory Effects Of mentioning
confidence: 67%
“…In addition, it was demonstrated that endogenous growth hormone and IGF-1 play an essential role in the therapeutic effect of ghrelin in acute pancreatitis [239]. Furthermore, in vitro studies performed on isolated rat acinar cells or rat pancreatic acinar tumor cell line AR42J have shown that the incubation of these cells with cerulein reduces the expression of ghrelin and the ghrelin receptor at the mRNA and protein levels [240]. On the other hand, the administration of ghrelin, in animals before the isolation of acinar cells, led to an increase in the expression of ghrelin and the ghrelin receptor in these isolated cells and reversed the cerulein-induce inhibition of their expression.…”
Section: Protective Therapeutic and Anti-inflammatory Effects Of mentioning
confidence: 99%